Implementasi Kurikulum Merdeka Belajar di SMP Katolik Santu Petrus Tumaluntung - Domensili, Christina; Pangkey , Itje; Terry , Hetreda; Tuerah, Paulus Robert (Abdurrauf Science and Society, 2025)
The purpose of this study was to analyze the perceptions of teachers in the implementation of the independent learning curriculum at SMP Katolik Santu Petrus Tumaluntung and the factors that hinder the implementation of the independent learning curriculum at SMP Katolik Santu Petrus Tumaluntung. The research method used in this study is qualitative research with data collection techniques through observation, documentation, and interviews. The data sources are the principal and teachers at SMP Katolik Santu Petrus Tumaluntung. The results of the study indicate that the perceptions of teachers in the implementation of the independent learning curriculum at SMP Katolik Santu Petrus Tumaluntung obtained positive conclusions because the teachers at SMP Katolik Santu Petrus Tumaluntung were able to implement the independent learning curriculum and were able to adapt to the independent learning curriculum. In addition, the perceptions of teachers at SMP Katolik Santu Petrus Tumaluntung have several indicators in the implementation of the independent learning curriculum, including: teacher perceptions of learning planning, learning implementation, assessment techniques in the independent learning curriculum and factors that hinder the implementation of the independent learning curriculum are the quality of human resources that are less than optimal, lack of teacher readiness in implementing the independent learning curriculum and the lack of training that can be followed by teachers Abstrak: Tujuan penelitian ini adalah untuk menganalisis tentang persepsi guru dalam implementasi kurikulum merdeka belajar di SMP Katolik Santu Petrus Tumaluntung dan faktor-faktor yang menghambat implementasi kurikulum merdeka belajar di SMP Katolik Santu Petrus Tumaluntung. Metode penelitian yang digunakan pada penelitian ini adalah penelitian kualitatif dengan teknik pengumpulan data melalui observasi, dokumentasi, dan wawancara. Sumber data adalah kepala sekolah dan guru di SMP Katolik Santu Petrus Tumaluntung. Hasil penelitian menunjukkan bahwa Persepsi guru dalam implementasi kurikulum merdeka belajar di SMP Katolik Santu Petrus Tumaluntung didapatkan kesimpulan yang positif karena guru yang ada di SMP Katolik Santu Petrus Tumaluntung mampu menerapkan kurikulum merdeka belajar dan mampu menyesuaikan diri dengan kurikulum merdeka belajar. Selain itu juga persepsi guru di SMP Katolik Santu Petrus Tumaluntung memiliki beberapa indikator dalam implementasi kurikulum merdeka belajar antara lain: persepsi guru terhadap perencanaan pembelajaran, pelaksanaan pembelajaran, teknik penilaian pada kurikulum merdeka belajar dan faktor–faktor yang menghambat dalam implementasi kurikulum merdeka belajar adalah mutu sumber daya manusia yang kurang maksimal, kurangnya kesiapan guru dalam implemetasi kurikulum merdeka belajar dan masih kurangnya pelatihan yang dapat diikuti oleh guru. Kata Kunci: Implementasi, Kurikulum Merdeka Belajar, Persepsi Guru